Embedded imperatives in kajkavian dialects of Croatian - Galić, Josip, filolog (Array, 2019)
Embedded imperatives are cross-linguistically very rare. They are attested, for instance, in modern languages such as Slovenian and High German and historical languages such as Ancient Greek and Old Scandinavian. In the literature, it has long been established that imperatives can also be embedded in some Kajkavian dialects of Croatian, but to date, this phenomenon has not been thoroughly analyzed. The paper deals with the material collected by field research and analyses it within the framework of Medeiros’ (2015) minimalist approach to embedded imperatives, according to which the embedding of imperatives is possible only in the languages in which imperative morphology does not depend on the directive operator. In the researched Kajkavian dialects, embedded imperatives can occur only in complement clauses, but older texts show that in the written language, embedded imperatives are also possible in relative clauses. Unlike many other languages in which imperatives may be embedded, in the researched Kajkavian dialects, embedding is relatively free. Both true and surrogate imperatives may be embedded, the subject of embedded clauses can be null and overt and does not necessarily have to co-refer to the internal argument of the matrix predicate.